Selection of Mice for Object Permanence Cognitive Task Solution - Olga Viktorovna Perepelkina; Inga Igorevna Poletaeva (MDPI AG, 2022)
The selection of mice for high ("plus") and low ("minus") scores in the puzzle-box test was performed over five generations. This test evaluates the success (or failure) in finding the underpass, leading to the dark part of the box, when it is blocked. This means that the mouse is either able or unable to operate the "object permanence rule" (one of the index's cognitive abilities). For the "+" strain, animals were bred who solved the test when the underpass test blocked with a plug; the "−" strain comprised those who were unable to solve this task. In mice of the "+" strain, the proportion of animals that was able to solve "plug" stages of the test was higher than in the "−" strain and in the non-selected genetically heterogeneous population. The "+" mice ate significantly more new food in the hyponeophagia test. Animals of both strains demonstrated the ability to "manipulate" the plug blocking the underpass, touching the plug with their paws and muzzle, although the majority of "−" mice were unable to open the underpass effectively. Thus, mice of both selected strains demonstrated that they were able to understand that the underpass does exist, but only "+"-strain animals (at least the majority of them) were able to realize the solution. The selection for plug-stage solution success affected the mouse's ability to open the hidden underpass.